District laboratory Practice in Tropical Countries - Cheesbrugh, Monica (Cambridge : Cambridge university, 2008)
This practical bench manual has been produced to help those working in the district laboratory, and those responsible for the organization and management of community laboratory services and the training of district laboratory personnel
Keywords: Medical Laboratories -- Developing Countrris; Tropical medicine -- Handbooks, manuals, etc; Diagnosis, Laboratory -- Handbooks, manuals; Medical laboratories -- Developing countries; Health Service Areas -- Developing Countrris; Dtagnosis Laboratory -- Handbooks; Dtagnosis Laboratory -- Manuals